2021
DOI: 10.1371/journal.pone.0246425
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changing foot progression angle using real-time visual feedback on rearfoot eversion during running

Abstract: Atypical rearfoot in/eversion may be an important risk factor for running-related injuries. Prominent interventions for atypical rearfoot eversion include foot orthoses, footwear, and taping but a modification derived from gait retraining to correct atypical rearfoot in/eversion is lacking. We aimed to investigate changes in rearfoot in/eversion, subtalar pronation, medial longitudinal arch angle, and selected lower limb joint biomechanics while performing toe-in/toe-out running using real-time visual feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These differences in movements in the transverse plane could also be related to the foot progression angle. A toe-out (foot abduction) placement during the stance phase of gait has been shown to increase the forefoot abduction angles ( Schallig et al, 2020 ) and can lead to increased foot pronation during running ( Mousavi et al, 2021 ). However, we did not directly measure the foot progression angle in our study, therefore we cannot confirm this association, and the lack of discriminating features in frontal plane movement between clusters suggests that it is unlikely that inter-cluster differences are solely related to that parameter.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in movements in the transverse plane could also be related to the foot progression angle. A toe-out (foot abduction) placement during the stance phase of gait has been shown to increase the forefoot abduction angles ( Schallig et al, 2020 ) and can lead to increased foot pronation during running ( Mousavi et al, 2021 ). However, we did not directly measure the foot progression angle in our study, therefore we cannot confirm this association, and the lack of discriminating features in frontal plane movement between clusters suggests that it is unlikely that inter-cluster differences are solely related to that parameter.…”
Section: Discussionmentioning
confidence: 99%
“…MLAA and increased internal longitudinal arch compared to normal and toe-out running. These 2 studies showed that the foot is more supinated when toeing-in [55,62]. Thus, in individuals with over-pronation, toeing-in not only may reduce foot pronation, it may contribute to foot stabilization at touchdown and late stance phase of walking.…”
Section: Plos Onementioning
confidence: 97%
“…Two studies assessed the effect of changing foot progression angle on rearfoot kinematics [62,63]. In the study by Mousavi et al [62] subjects performed toe-in/toe-out running using Toe-in running decreased peak rearfoot eversion, peak pronation, and peak medial longitudinal arch angle (MLAA) in healthy runners [17].…”
Section: Changing Foot Progression Anglementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, externally rotated FPA and increased medial loading play important roles in flatfoot [ 21 , 22 ]. Moreover, foot placement angle was the best single predictor of total rearfoot motion, and the FPA may be useful to correct atypical rearfoot kinematics [ 23 , 24 ]. Classifying the left foot and the right before measuring the FPA may play an important role in providing information on the postural changes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%